Diversification of Processed Food Products Based on Papaya in Improving Community Welfare sub-district Karang Joang, Balikpapan, East Kalimantan - Amaliah, Nur; Setyawati, Ria; Farida, Farida; Suriana, Ida; Gafur, Abdul (Universitas Nusantara PGRI Kediri, 2019)
One of the Rukun Tetangga which is the center of papaya in Balikpapan City is RT 19 Kelurahan Karang Joang Balikpapan Utara. The potentials of papaya fruit reach 10 tons per month or around 140 tons in a year. Papaya agricultural land continues to grow 10 to 20 percent. The problem is that farmers only sell their papaya in a fresh condition, even many are damaged due to too much harvest and not sold in the market. The community does not know about the use of papaya in product development so that the method used to solve the problems of the Karang Joang community, especially RT 19, is to socialize and provide materials related to food diversification. The results obtained from this community service are giving material and understanding to the women of Cempaka 19 farming women regarding the processing of papaya and training in making products including making abon and semprong papaya, and providing assistance in processing equipment to support the production of women mothers Cempaka 19 farm.